An Analysis of Presupposition Triggers in â€œTurning Redâ€ - Dian Fitriani; Mhd. Johan (Institut Agama Islam Negeri Palopo, 2023)
This research analyzes the triggers of the presuppositionÂ that can be discovered in the movie